2010
DOI: 10.1097/bco.0b013e3181f20439
|View full text |Cite
|
Sign up to set email alerts
|

Specific staphylococcal polymerase chain reaction can be a complementary tool for identifying causative organisms and guiding antibiotic management in orthopaedic infections

Abstract: BackgroundVast numbers of bone and joint infections in adults, including prosthetic joint infections, are caused by staphylococci. Because of the complexity of these infections, treatment with broadspectrum antibiotics active against staphylococci usually is started before sampling. This may be one of the reasons why conventional microbiology cultures fail to identify a causative organism. We sought to demonstrate that a specific duplex Staphylococcus species real-time polymerase chain reaction can aid in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 23 publications
(7 reference statements)
0
16
0
Order By: Relevance
“…The five-well multiplex real-time PCR assays were designed in conjunction with the Health Protection Agency Newcastle for this study (unpublished, S . aureus and MRSA and gap assays taken from existing literature [ 42 , 43 ]), and the primers and probe sequences used in these assays are shown in S1 Table .…”
Section: Methodsmentioning
confidence: 99%
“…The five-well multiplex real-time PCR assays were designed in conjunction with the Health Protection Agency Newcastle for this study (unpublished, S . aureus and MRSA and gap assays taken from existing literature [ 42 , 43 ]), and the primers and probe sequences used in these assays are shown in S1 Table .…”
Section: Methodsmentioning
confidence: 99%
“…To confirm the results obtained for pathogen target ArrayTube TM hybridizations, pathogen-specific RT-PCR assays were used. Multiplex meningitis-associated pathogen real-time PCR assays were constructed based on either previously published assays for many of the bacterial pathogens represented on the array e.g., Group B Streptococcus [79], H. influenzae [21,80], S. aureus [81], S. epidermidis [2], N. meningitidis [14,82] and S. pneumoniae [83], or in house designed PHE assays, where existing previously published assays were not available. Real-time PCR assays to the meningococcal capsular transport gene ctrA were used for N. meningitidis , as previously described [21].…”
Section: Methodsmentioning
confidence: 99%
“…However, only three out of 10 patients had their antibiotics modified according to the PCR result, including escalation to broader spectrum antibiotics to cover for methicillin-resistant Staphylococcus aureus, based on a positive PCR. The rest of the cases were already on antibiotics clinically deemed appropriate and were not changed based on the PCR result [18].…”
Section: Impact Of Pcr On Antimicrobial Management In Pjimentioning
confidence: 99%
“…In most studies, it is clear that PCR has shown considerably higher sensitivity compared with conventional tissue culture for detecting pathogens in the diagnosis of PJI [6,11,[15][16][17][18][19][20][21][22][23][24] and most recent studies (published in the last 3 years) are summarized in (TABLE 1). One of the earlier prospective studies compared PCR and culture techniques from synovial fluid, which included 115 cases of potential PJI.…”
mentioning
confidence: 99%